LEGAL PROTECTION AGAINST THE FAILURE TO COMPENSATE ON INTERNATIONAL INVESTMENT DISPUTE - Vunieta, Vunieta; Haque, Walida Ahsana (Yustisia, 2019)
A dispute between two or more countries involved in a foreign investment may arises from investment agreement agreed upon by the parties. If one of the parties breaches the agreement, the parties will automatically agree to resolve the dispute to the agreed arbitration forum based on the dispute settlement clause on the agreement, those forum such as the ICSID arbitration. Therefore, the existence of dispute settlement clause on an investment agreement (Bilateral Investment Treaty) is very necessary. The result of the above-mentioned arbitration proceeding is a binding and final decision for the parties. An arbitral award, should contain relief or compensation set by the arbitrator as the result of the proceeding. The reliefs are given as orders to indemnify the damages obtained by Claimant. Issues arises when Respondent has been proven to have done detrimental damage to the Claimant yet Respondent deliberately neglected his/her obligation to compensate Claimant accordingly based on the relief/ compensation specified in the award. The non-compliance of the Respondent to fulfill the compensation obligation is due to the fact that the party habitually assume that the arbitration award does not have the legal force equivalent to the decision of general court, even though the nature of the award is final and binding. Thus the interests and rights of the Applicant who has been declared entitled to compensation based on the arbitration award must be protected so that their rights can be fulfilled according to the law.